Eastern Hemlock (Tsuga canadensis) as a new host of Pityokteines spinidens in the arboretum in Europe - Tomáš Fiala; Jaroslav Holuša (Plant Protection Science)
Bark beetle Pityokteines spinidens (Coleoptera: Curculionidae: Scolytinae) is widespread across Europe. We identified this species as a pest of Tsuga canadensis in western Bohemia's Americká zahrada National Nature Monument Arboretum. This discovery suggests that P. spinidens could infest any conifer within the Abietoideae subfamily. Given its status as a known pest of various Abies species, its potential impact on related conifers warrants further attention.